Patient-Derived Xenograft Models of Colorectal Cancer: Procedures for Engraftment and Propagation - Burgenske, Danielle M; Monsma, David J; MacKeigan, Jeffrey P (Methods in molecular biology (Clifton, N.J.), 2018)
Preclinical compounds tested in animal models often demonstrate limited efficacy when transitioned into patients. As a result, individuals are assigned to treatment regimens that may be ineffective at treating their disease. The development of more clinically relevant models, such as patient-derived xenografts (PDXs), will (1) more completely mimic the human condition and (2) more accurately predict tumor responses to previously untested therapeutics.PDX models are clinically relevant as tumor tissue is implanted directly from human donor to the mouse recipient. Therefore, these models prevent cell population selection, intentional or unintentional, as the human tissue adapts to an in vitro, two-dimensional environment prior to implantation into a three-dimensional in vivo murine host. Often, cell heterogeneity and tumor architecture can be maintained from human to the PDX model in the mouse. This protocol describes the engraftment and propagation processes for establishing colorectal (CRC) PDX models in mice, using tumor tissue from human subjects.